Women and Mass Media Development in the 21st Century: Viz A Viz - Oluwaseun S. Osadola; Foluso O. Oyewumi; Ifedapo O. Osadola (Budapest International Research and Critics University, 2022)
Women have employed the various channels of communication that covers broadcasting, newspapers, television, radio, internet for creating awareness, to express opinions, to educate the general public and enlighten women themselves on their rights and privileges. The current state of the media as against what existed in the pre-colonial and colonial era has triggered participation of women in the development of the sector. While there are bourgeoning literatures on women generally, their role in education, home, economy, governance, agriculture, food security, child bearing and rearing, a narrower study focuses on the role of women in the development of mass media from a historical perspective, thus creating a gap in literature. To this end, this study delves into a historical appraisal of women and mass media development in the 21st century. The paper reviews existing debates on women and mass media development and goes further to assess their contributions to one another.